BARRIERS TO INTEGRATING CLIMATE CHANGE ADAPTATION INTO URBAN DEVELOPMENT IN INDONESIA - Wijaya, Nurrohman (PEOPLE: International Journal of Social Sciences, 2015)
Rapid urbanization as a process of urban development creates an opportunity for the municipalities to boost their economic status. However, there is an increased attention of the risks resulting from climate change. The cities become a hotspot of vulnerability. Integrating climate change adaptation into urban development becomes important as a key policy response to climate change in the context of developing countries. The purpose of this study is to explore barriers to integrating climate change adaptation into urban development in Indonesia. Desk study and semi-structure questionnaire with selected key informants are conducted. The Weight Average Index is used to quantify the degree of barriers. The results reveal that overall barriers are categorized as a high score. The barriers are mainly related to knowledge and information concerns. However, social and behavioral barriers are also significance. Strategies to overcome the identified barriers are recommended, most importantly the need for building the capacity of all stakeholders, increasing a better understanding and awareness of municipality authorities, and getting acceptance and participation from the public. This study can be useful for planning and implementation of policy measure in climate change adaptation and urban development.